Application of Work Ethics and Performance of Public Service in Southeast, Nigeria - Oluwatoyin, Owolabi Yetunde; Ayodele, Nwaodike Chibuzor; Oni, Michael Abiodun (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Governments across the world adopt work ethics to promote efficiency and effectiveness in the performance of public service. This is expected to meet the needs and aspiration of the populace. Some states in Southeast Nigeria, particularly Ebonyi, Enugu and Imo public services though have ethical conduct stipulated in public service rules, ironically, application of the work ethics have not resulted to the expected performance of service delivery. The study adopted Descriptive research design. The population was the public service in Ebonyi, Enugu and Imo state, Nigeria. The three states were purposively selected with numerical population of 51,102. Stratified and simple random sampling techniques were used to select three MDAs (Ministry of Works and Infrastructure/Transport, Civil Service Commission and Water Corporation). The sample size was 786. Questionnaire was the major instrument of data collection complemented by interview guide. Reliability test of the instrument yielded Cronbachâ€™s alpha coefficients for the construct ranging from 0.77 to 0.82. The response rate was 87%.  Data collected were tabulated, while mean as well as standard deviation were calculated and content analysed. Findings revealed that Public service in the three states were bedevilled with corrupt practices, inadequate funding, lack of regular on the job training, and unconducive political environment. Therefore, performance of public service were short of expectation. The study recommended adequate punitive mechanism to sanction any misconduct, adequate funding, regular training and development, political will to implement governmental policy. Keywords : Work Ethics, Public Service, Performance, Code of Conduct, Southeast